1981
DOI: 10.1080/03015521.1981.10427794
|View full text |Cite
|
Sign up to set email alerts
|

Grazing behaviour of merinos on an undeveloped semi-arid tussock grassland block

Abstract: Flocks of merino wethers or ewes varying in size from 20 to 2200 were observed from dawn until dusk for 77 days over three summers on an 850 ha block of undeveloped, semi-arid Festuca novae-zelandiae tussock grassland with an altitudinal range of 60 m.Group location, size, and activity were recorded at half-hourly intervals together with associated weather. Sheep dispersed at dawn, grazed during the morning (about 80% at anyone time), rested during the middle of the day (standing, lying, or in shade groups; to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…However, the activity and utilization patterns of sheep grazing freely on open range and in forests have received less attention (Noble 1975). Many such studies have involved fenced, sown, and fertilized pasture (Hunter 1962, Lynch 1971, De Leeuw and Bakker 1986 and major predators have been absent (Grubb andJewel1 1974, Scott andSutherland 1981).…”
mentioning
confidence: 99%
“…However, the activity and utilization patterns of sheep grazing freely on open range and in forests have received less attention (Noble 1975). Many such studies have involved fenced, sown, and fertilized pasture (Hunter 1962, Lynch 1971, De Leeuw and Bakker 1986 and major predators have been absent (Grubb andJewel1 1974, Scott andSutherland 1981).…”
mentioning
confidence: 99%
“…Whether effective conditioning or learning from contrived experience is possible was not examined in this study. The research of Scott & Sutherland (1981) suggests it is not likely to occur simply by exposure of sheep to small unfenced plots (three of 0.25 ha) of improved grassland, even though the present study shows a substantial effect on sheep distribution from topdressing and oversowing a total area of 44 ha in a study area of similar size.…”
Section: Sheep Distributionmentioning
confidence: 77%
“…Harris & O'Connor (1980) found little New Zealand-based scientific information on relationships between forage supply, forage improvement, and sheep behaviour. Scott & Sutherland (1981) reported the effect on sheep behaviour of developing three 0.25 ha areas in a relatively flat 850 ha undeveloped block of semi -arid tussock grassland in the Mackenzie Basin, Canterbury. That study suggested sheep retained no memory from day to day of the location of these developed sites.…”
Section: Introductionmentioning
confidence: 99%
“…Das Verhaltensmuster ist für afrikanische Wiederkäuer beschrieben (34), lässt sich aber auch bei unseren Tieren beobachten. Einen ähnlichen Effekt hat das enge Beieinanderstehen bei Hitze (78,88). Oft halten die Schafe ihren Kopf gesenkt, um ihn der direkten Sonneneinstrahlung zu entziehen (14,78) (88).…”
Section: Spengler: Wasserbedarf Kleiner Wiederkäuer Bei Weidehaltungunclassified
“…Einen ähnlichen Effekt hat das enge Beieinanderstehen bei Hitze (78,88). Oft halten die Schafe ihren Kopf gesenkt, um ihn der direkten Sonneneinstrahlung zu entziehen (14,78) (88). Schwitzen und Hecheln erhöhen den Wasserbedarf, der eng mit der Atemfrequenz verknüpft ist.…”
Section: Spengler: Wasserbedarf Kleiner Wiederkäuer Bei Weidehaltungunclassified